ANALISIS TENTANG RESTRUKTURISASI KREDIT UNTUK MENGHINDARI TERJADINYA KREDIT MACET (STUDI PADA BANK RAKYAT INDONESIA (PERSERO) TBK CABANG LUBUK PAKAM - AAN TRIANDI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. T. Keizerina Devi A3. Suprayitno Debt restructuring is one of the efforts to repair the credit quality to prevent a default. The Law No. 10/1998 is known as credit default redemption system as stipulated in Article 7 paragraph c. The objective of the research was to discover the mechanism of restructuring in conventional banks, to find out the criteria of problem credit that can be restructured, and to discover and analyze the process of restructuring in the Lubuk Pakam Branch Office of PT. Bank Rakyat Indonesia (Persero) Tbk. This is a normative legal research with descriptive analysis. The data studied consist of primary legal materials such as the civil laws and the law no. 10/1992 on the amendment of the Law No. 7/1992 on Banking and field research. The theory of Legal Certainty is applied in this thesis. The research employed qualitative method for the data analysis. The results of the research find out that credit is one of banking products that provides many advantages to banks, yet it has the highest risk as well among the other banking products. In case of problem credits, there are efforts to safe them from becoming credit default i.e. debt restructuring.Keywords: Bank;Credit Default;Restructuring.